MUNIFICENCE OF THE ARISTOCRATS OF ROMAN TRIPOLITANIA (2002)
Many authors such as Banaji (2002; 2015), Mattingly (2003), and Cherry (1988), have variously discussed Rome’s policies in Roman Tripolitania as well as economic and agricultural progress of Tripolitania which was aided and controlled by the aristocrats of the region. This study, however, aims to examine munificence in the form of donations by aristocrats of Roman Tripolitania from their largesse towards their patriae (fatherland). These donations ranged from beautification to erections of some monuments in their cities. This paper intends to examine, using data in the form of Latin inscriptions, munificence of the elites of the region. The data for this study is sourced from the Inscriptions of Roman Tripolitania (IRT). The paper adopts a methodology that is historical as it throws light on status of men and the munificence of the aristocrats of Roman Tripolitania. The paper argues that the munificence of the aristocrats of the region was one of the obligations of men of such high economic and social standing. The study further argues that in exchange of the donations, aristocrats earned recognition in the form of political allegiance from the citizens and the states. Further studies that may examine social status in Roman Tripolitania are recommended.